The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/bjs.4072
|View full text |Cite
|
Sign up to set email alerts
|

High recurrence rate after atypical resection for pancreatic metastases from renal cell carcinoma

Abstract: Despite the slow development of these secondaries and their well encapsulated morphology, the high rate of recurrence after limited resection suggests that radical resection should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
1
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 17 publications
(23 reference statements)
3
116
1
10
Order By: Relevance
“…Bassi et al found a higher rate of morbidity and local recurrence after atypical resections, and consequently advised standard resections for all pancreatic metastases [6]. However, other authors did not find any statistically significant difference in outcomes when comparing standard versus atypical resections [12,21,23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassi et al found a higher rate of morbidity and local recurrence after atypical resections, and consequently advised standard resections for all pancreatic metastases [6]. However, other authors did not find any statistically significant difference in outcomes when comparing standard versus atypical resections [12,21,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 4 featured patient populations that overlapped with subsequent, larger studies, and 12 were rejected because they did not fulfil the inclusion criteria. The remaining 18 studies met the above criteria to merit inclusion in the extractable and analysable dataset [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The search strategy and outcomes are summarised in Figure 1.…”
Section: Search Yields and Data Retrievalmentioning
confidence: 99%
“…In patients with pancreatic metastases from RCC, absence of extrapancreatic metastases and limited vascular involvement, 2 and 5 years survival rates of 78% and 65%, respectively after resection of pancreatic disease are reported [3,4]. In our patients, radical nephrectomy and distal pancreatectomy were performed without complications.…”
Section: Discussionmentioning
confidence: 68%
“…Their incidence in autopsy series has been reported as 1-3% in patients with primary RCC and their diagnosis is often radiological [1]. Early detection of RCC pancreatic metastases, frequently performed by multidetector computed tomography (MDCT) dut to the imaging pattern of hyperenhancing lesions allows for appropriate treatment and improved outcomes for metastatic disease [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with RCC, up to 30% have metastases at presentation, and 40À50% will develop widespread metastatic disease over time (3). The long-term (5-year) survival rate is 10À15% once metastases have spread (1).…”
Section: Introductionmentioning
confidence: 99%